2010
DOI: 10.2337/db09-1618
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin (MK0431) Inhibition of Dipeptidyl Peptidase IV Decreases Nonobese Diabetic Mouse CD4+ T-Cell Migration Through Incretin-Dependent and -Independent Pathways

Abstract: OBJECTIVETreatment of NOD mice with the dipeptidyl peptidase-IV (DPP-IV) inhibitor sitagliptin preserved islet transplants through a pathway involving modulation of splenic CD4+ T-cell migration. In the current study, effects of sitagliptin on migration of additional subsets of CD4+ T-cells were examined and underlying molecular mechanisms were further defined.RESEARCH DESIGN AND METHODSEffects of sitagliptin on migration of NOD mouse splenic, thymic, and lymph node CD4+ T-cells were determined. Signaling modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 53 publications
0
40
0
2
Order By: Relevance
“…DPP IV (CD26) is known to modulate immune function, T cell proliferation, and macrophage migration (28,45), and DPP IV inhibition reportedly reduced inflammatory cytokine production by the T cells and inhibited transendothelial migration of the latter (27,45). Interestingly, a recent study showed that sitagliptin decreases NOD mice CD4ϩ T cell migration through incretin-dependent and -independent pathways (30). We showed that sitagliptin reduced macrophage infiltration in adipose tissue.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…DPP IV (CD26) is known to modulate immune function, T cell proliferation, and macrophage migration (28,45), and DPP IV inhibition reportedly reduced inflammatory cytokine production by the T cells and inhibited transendothelial migration of the latter (27,45). Interestingly, a recent study showed that sitagliptin decreases NOD mice CD4ϩ T cell migration through incretin-dependent and -independent pathways (30). We showed that sitagliptin reduced macrophage infiltration in adipose tissue.…”
Section: Discussionmentioning
confidence: 82%
“…Immune cell infiltration, notably of different subpopulations of macrophages and T cells, was recently shown to correlate with the development and maintenance of insulin resistance and diabetes in obesity (8,26,41,56). Recently, sitagliptin treatment in nonobese diabetic mice was shown to decrease CD4ϩ T cell migration through incretindependent and -independent mechanisms (30). Also, DPP IV is increased in blood monocytes of obese human subjects (35).…”
mentioning
confidence: 99%
“…GLP1 receptor activation has been shown to directly reduce apoptotic cell death after exposure to a diverse number of toxins and cytokines that are likely to contribute to b-cell destruction (Buteau et al 2004). In addition, lymphocytes contain significant amounts of membrane-bound DPP4 (Engel et al 2003), and both splenic DPP4 responsive and lymph node incretin non-responsive T-cell lymphocytes have been shown to infiltrate islets of diabetic NOD mice leading to b-cell destruction (Kim et al 2010). Thus, DPP4 inhibition may exert anti-inflammatory effects in the pancreatic islets in addition to an insulinotropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Kutoh (2011) reported beneficial effects of the DPP4 inhibitor sitagliptin as add-on therapy to insulin in reducing BG levels in a small sample of patients with T1D. In addition, sitagliptin was shown to preserve islet transplants in non-obese diabetic (NOD) mice (Kim et al 2009(Kim et al , 2010). This mouse model spontaneously develops a form of insulin-dependent diabetes similar to the human disease (Delovitch & Singh 1997, Anderson & Bluestone 2005.…”
Section: Introductionmentioning
confidence: 99%
“…DPP-IV degrades a large quantity of molecules, including multiple chemokines involved in the innate immune response, and DPP-IV inhibition has been shown to have direct inhibitory effects on CD4-positive T cell and monocyte migration, all of which are involved in atherogenesis [7][8][9][10]. In addition, clinical data suggest that DPP-IV inhibitors influence various cardiovascular risk factors associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%